2016
DOI: 10.1209/0295-5075/116/38004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interactions between depletants in phase diagrams of binary hard-sphere systems

Abstract: Fluid-solid phase diagrams for binary hard-sphere systems were calculated to study the effects of interactions between depletants. Two effective potentials between large hard spheres were examined. One was the Asakura-Oosawa (AO) potential, and the other was an effective potential obtained by using an integral equation theory (IE potential). The IE potential has oscillations caused by the interactions between depletants, whereas in the AO potential, the inter-depletant correlation is ignored. The phase diagram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…In the Asakura–Oosawa model, the depletants are treated as ideal with no structural correlations. Taking into account a hard sphere interaction between depletants as in the case of the α‐crystallin proteins, this can cause an oscillation in the effective attractive potential . This results in a repulsive barrier that grows larger with increased depletant concentration and reduces the probability of particles to reach the potential well upon collision .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Asakura–Oosawa model, the depletants are treated as ideal with no structural correlations. Taking into account a hard sphere interaction between depletants as in the case of the α‐crystallin proteins, this can cause an oscillation in the effective attractive potential . This results in a repulsive barrier that grows larger with increased depletant concentration and reduces the probability of particles to reach the potential well upon collision .…”
Section: Resultsmentioning
confidence: 99%
“…Taking into account a hard sphere interaction between depletants as in the case of the α‐crystallin proteins, this can cause an oscillation in the effective attractive potential . This results in a repulsive barrier that grows larger with increased depletant concentration and reduces the probability of particles to reach the potential well upon collision . This converts the diffusion‐controlled aggregation, where every collision event leads to an irreversible binding between particles, to a reaction‐controlled situation, where the probability of a collision leading to irreversible binding exponentially decreases with increasing potential barrier.…”
Section: Resultsmentioning
confidence: 99%
“…For a long time, it was believed that binary hard-sphere mixtures are thermodynamically stable for all concentrations and size ratios, 26 until Biben and Hansen 27,28 first showed that phase separation can occur in binary hard-sphere mixtures. This finding was later confirmed by a variety of theoretical approaches, [29][30][31] simulation studies, 23,32,33 and experimental works. 34,35 A historical overview of studies on binary hardsphere mixtures can be found in Ref.…”
Section: Introductionmentioning
confidence: 63%
“…For a long time it was believed that binary hard-sphere mixtures are thermodynamically stable for all concentrations and size ratios 26 , until Biben and Hansen 27,28 first showed that phase separation can occur in binary hard-sphere mixtures. This finding was later confirmed by a variety of theoretical approaches [29][30][31] , simulation studies 23,32,33 and experimental works 34,35 . A historical overview of studies on binary hard-sphere mixtures can be found in 33 .…”
Section: Introductionmentioning
confidence: 67%